Utilization Of Illustated Booklet Educational Methods For Early Detection Of Risk Factors In Pregnancy - Syastriani Isna Putri Syarif (CV. Syntax Corporation Indonesia, 2023)
Low public knowledge and awareness to check pregnancy to health workers causes many risk factors complications that accompany pregnancy while pregnant women are required to do pregnancy checks during their pregnancy period at least 4 times, namely 1 time trimester I, 1 time trimester II, and 2 times trimester III. This study aims to determine the effect of Intervention Illustrated Booklet Educational Methods On Women's Knowledge Of Prenatal Care on early detection of risk factors in pregnancy. The type of research used in this study is quasi-experimental (pseudo-experiment) with Non Randomized pre-test-post-test control group design. The sampling technique is Exhaustive sampling totaling 60 people. Where there are 2 groups (Intervention and Control) each group totaling 30 respondents. The hypothesis in this study is that there is an effect of the Illustrated Booklet Educational Methods On Women's Knowledge Of Prenatal Care on improving acting situations, increasing motivation for personal autonomy and increasing social support for husbands and families of pregnant women at the Kioko Health Center. The results showed that there were differences and influences of situations acting knowledge (p = 0.046) attitudes (p = 0.014), personal autonomy of knowledge (p = 0.005) while attitudes of personal autonomy (p = 0.059), and social support of husband and family knowledge (p = 1) attitudes (p = 1) there was no difference and influence before and after getting the intervention. The conclusion of this study is that there is an influence of the Illustrated Booklet Educational Methods On Women's Knowledge Of Prenatal Care on improving the situation of acting pregnant women, there is an influence of the Illustrated Booklet Educational Methods On Women's Knowledge Of Prenatal Care on increasing the motivation of personal autonomy of pregnant women and there is no influence of the Illustrated Booklet Educational Methods On Women's Knowledge Of Prenatal Care on the support of husbands and families of pregnant women.